SHEA PICKING AS AN ENGINE OF POVERTY REDUCTION IN NORTHERN GHANA (CASE STUDY: FOUR COMMUNITIES IN THE BOLGATANGA MUNICIPALITY) - Hatskevich, A.; Essilfie, J. E. (European Scientific Journal, ESJ, 2013)
Peasant farming had been seen for many years as a means of fighting rural poverty in the Sub-Saharan zone of Africa. With the passing of time, new researches had shown that the notion is fading off since studies have established that only a small percentage of those farms have seen expansion and intensification leaving the rest stagnated with lowing productivity, decrease in size and low output. Alternative sources of rural income are therefore important to determine for specific locations. This paper looks at the effects of shea picking on rural household income in four (4) communities in the Sumbrungu area of the Bolgatanga Municipality of the Upper East Region of Ghana. Regression analysis performed indicated that shea picking activity in the selected communities is a signification source of income as compared to the official minimum dairy wage in Ghana. The main factors that influence income of shea-picker household are the age of the picker and the quantity of shea fruits picked per day and an interaction between shea quantity and location of community with respect to Bokom community. Income distribution among interested households under this work appeared to be well distributed which indication that a common taughtfully designed poverty reduction strategy could be rolled out in all the communities in the area and among all shea-picker households.